A microwave-promoted atom-efficient diesterification of aromatic carboxylate with 1, 4-dibromobutane in water. Issue 19 (2nd October 2018) - Ding, Shenglong; Bai, Lin; Cong, Yong; Chen, Ting
Abstract: A rapid and efficient diesterification reaction of aromatic carboxylate with 1, 4-dibromobutane was carried out in water at 100 °C in the presence of base and phase transfer catalyst under focused microwave irradiation. This microwave-promoted protocol offers an atom-efficient and environment-friendly approach to synthesize butamethylenediesters in high yield. Graphical Abstract: